The relationships between demographic variables and risk-taking behaviour among young motorcyclists - Md Nor, Siti Maryam; Abdullah, Haslinda (Universiti Putra Malaysia Press, 2014)
In a previous study, it is well documented that adolescents are more likely than adults to engage in risky behaviour (Arnett, 1992). Most evidence suggests that risk-taking is the most important major factor underlying the high crash rates among teens. The objectives of this study were: 1) to examine the extent of risk-taking behavior of Malaysian motorcyclists, and 2) to investigate the relationship between demographic variables of motorcyclists and risk-taking behavior. A total of 540 respondents from six different areas in the Klang Valley (Jalan Kapar, Jalan Meru, Jalan Ampang, Lebuhraya Damansara Puchong, Jalan Tun Razak and Jalan Kuala Selangor-Sungai Buloh) were surveyed. The study found that there were significant gender differences in term of 'riding over speed limit' and 'riding without crash helmet'. In terms of age, there are significant differences between age and 'riding without crash helmet'. In terms of personal income, the result showed that there are significant differences between personal income and 'riding without crash helmet' and 'riding without headlights and not stopping at three-way junction'. However, there are no significant difference between race and highest education level and risk-taking behavior dimensions.